Spin freezing in the disordered pyrochlore magnet NaCaCo2F7: NMR studies and Monte Carlo simulations - Sarkar, R.; Krizan, J. W.; Brueckner, F.; Andrade, E. C. [UNESP]; Rachel, S.; Vojta, M.; Cava, R. J.; Klauss, H. -H. (Amer Physical Soc, 2017)
We present results of Na-23 and F-19 nuclear magnetic resonance (NMR) measurements on NaCaCo2F7, a frustrated pyrochlore magnet with a Curie-Weiss temperature Theta(CW) approximate to -140 K and intrinsic bond disorder. Below 3.6 K both the Na-23 and F-19 spectra broaden substantially in comparison to higher temperatures accompanied by a considerable reduction (80%) of the NMR signal intensity: This proves a broad quasistatic field distribution. The F-19 spin-lattice relaxation rate (19)(1/T-1) exhibits a peak at 2.9 K already starting to develop below 10 K. We attribute the spin freezing to the presence of bond disorder. This is corroborated by large-scale Monte Carlo simulations of a classical bond-disordered XY model on the pyrochlore lattice. The low freezing temperature, together with the very short magnetic correlation length not captured by the simulations, suggests that quantum effects play a decisive role in NaCaCo2F7.